Serotypic and biochemical characterization of Bacteroides nodosus isolates from Oregon. - Schmitz, J A (1980)
Ninety-seven Bacteroides nodosus isolates were characterized by the tube agglutination test. Fourteen serotypes were identified including isolates that were serologically similar to Australian serotypes A, B and C. One additional isolate remains untyped and possibly represents another serotype. The isolates were cultured from 20 different flocks. Multiple isolates were obtained from 15 of the flocks and 13 of these had two to seven different B. nodosus serotypes. Eleven B. nodosus isolates representing one Australian and ten Oregon serotypes were nonfermentative in various carbohydrates and did not produce indole. These isolates all exhibited proteolytic activity. The prototype strains of 12 of the 14 serotypes demonstrated virulence as assessed by an elastase production assay.